Relationship between anthropometric and dual energy X-ray absorptiometry measures to assess total and regional adiposity in Malaysian adolescents - Leng, Huat Foo; Pey, Sze Teo; Abdullah, Nurul Fadhilah; Aziz, Mohd Ezane; Andrew, P. Hills (Wiley, 2013)
The main objective of this paper was to determine the utility of various anthropometric measures to assess total and regional body fatness using dual-energy X-ray absorptiometry (DXA) as the criterion in 454 adolescent boys and girls aged 12-19 years. Multivariable regression analyses of gender-specific and gender-combined models were used to determine anthropometric measures on DXA-derived body fatness models, after adjusting for known confounding biological factors. Partial correlation analyses, after adjusting for age, pubertal growth status and ethnicity in boys and girls, showed that body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-height ratio (WhtR) were significantly correlated with total body fat (TBF), percent body fat (%BF), android region fat (ARF) and trunk fat (TF) (all p<0.0001). BMI was the greatest independent determinant, contributing 43.8%-80.9% of the total variance for DXA-derived body fatness models. Results confirmed that a simple anthropometric index such as the BMI is a good surrogate indicator of body fat levels in Malay and Chinese adolescents.